2014
DOI: 10.5455/musbed.20140902023654
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Pregnancy in Prenatal Period Women and Factors Associated With Adaptation

Abstract: Prenatal dönemdeki kadınların gebeliğe uyumu ve ilişkili faktörlerAmaç: Bu çalışmanın amacı, prenatal dönemdeki kadınların gebeliğe, annelik rolüne uyumu ve bu uyumu etkileyen faktörleri değerlendirmektir. Gereç ve Yöntem: Bu araştırma tanımlayıcı bir çalışmadır. Çalışmaya İstanbul Üsküdar'da prenatal dönemde bulunan 390 kadın dahil edilmiştir. Veriler Nisan 2012-Temmuz 2012 tarihleri arasında altı aile sağlığı merkezinde toplanmıştır. Veriler demografik soru formu ve Prenatal Kendini Değerlendirme Ölçeği kull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 5 publications
5
22
0
8
Order By: Relevance
“…Having a planned pregnancy increases adaptation to pregnancy. Demirbaş & Kadıoğlu () found an important association between AP, being ready for IMR and finding the strength to cope with possible problems. Demirbaş and Kadıoğlu's study supports our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having a planned pregnancy increases adaptation to pregnancy. Demirbaş & Kadıoğlu () found an important association between AP, being ready for IMR and finding the strength to cope with possible problems. Demirbaş and Kadıoğlu's study supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, it has been reported that women who have difficulty accepting pregnancy have a harder time adapting to pregnancy and motherhood and experience more fears related to childbirth (Demirbaş & Kadıoğlu ; Lederman & Weis ). However, this assumption was not supported by studies and no international nor national studies have examined the associations between AP, IMR, and FOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 In the literature, women who have diffi culty accepting pregnancy are reported to have more diffi culties in adapting to pregnancy and motherhood, and to develop negative attitudes towards pregnancy and the baby due to physical discomforts they experience. [12][13][14] Women who can express their feelings and who receive social support have been demonstrated to have less diffi culty in complying with the role of motherhood. 13 However, the way a pregnant woman expresses her feelings is affected by her beliefs, role in society, relationships with the spouse and other members of the family, fi nancial situation, expectations from life, level of education and philosophy of life, and the meaning attributed to pregnancy and the value of the child in society.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Women who can express their feelings and who receive social support have been demonstrated to have less diffi culty in complying with the role of motherhood. 13 However, the way a pregnant woman expresses her feelings is affected by her beliefs, role in society, relationships with the spouse and other members of the family, fi nancial situation, expectations from life, level of education and philosophy of life, and the meaning attributed to pregnancy and the value of the child in society. 6 In Turkey and in some cultures, there are practises that have a special meaning for the preparation of pregnant woman about sexual activity, birth and baby.…”
Section: Introductionmentioning
confidence: 99%